The Epistemology of Human Creation In The Qur'an - Ahmad Muaz; Dian Eka Seftiani; Ira Regista Rahmawati; Siti Hida Nuraidah; Fetrimen (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examines the epistemology of human creation in the Qur'an through a Systematic Literature Review (SLR) approach. The research aims to analyze the sources of knowledge, methods of understanding, and criteria of truth related to the concept of human creation from an Islamic perspective. Data were collected from various national and international scholarly articles relevant to Islamic epistemology, scientific exegesis, and the concept of human creation in the Qur'an. The findings reveal that the Qur'anic concept of human creation encompasses both biological and spiritual dimensions that are integrally interconnected. Revelation serves as the primary source of knowledge, while reason and empirical inquiry function as instruments for interpretation and contextualization. The stages of human creation, such as nutfah (drop of fluid), ‘alaqah (clinging substance), and mudghah (chewed-like lump), demonstrate conceptual relevance to modern embryology; however, they should not be regarded as absolute scientific equivalence. The study also finds that Islamic epistemology adopts an integrative framework through the bayani, burhani, and irfani approaches. Furthermore, the findings affirm that the relationship between revelation and science is complementary in nature. Consequently, the Qur'an should be understood not only as a source of divine guidance but also as an epistemological foundation for comprehending the nature of human beings in a holistic manner.